KEBIJAKAN PENILAIAN KEBERHASILAN REKLAMASI LAHAN PASCA-TAMBANG BATUBARA DI INDONESIA - Ardiyanto Wahyu Nugroho; Ishak Yassir (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2017)
Indonesian government has enacted regulations requiring reclamation and rehabilitation activities on post coal mining areas. However, the evaluation related to the ecological restoration concepts is yet unavailable. This study aims to evaluate the regulations on rehabilitation and reclamation of post coal mining areas in Indonesia conforming on ecological restoration concepts. Employing desk study and content anaysis, this research focussed on three technical regulations concerning reclamation guidance and post-mining evaluation guidance, namely ESDM Decree No 7 Year 2014, MoF Decree No P.60/Menhut-II/2009, and MoF Decree No P.4/Menhut-II/2011. Each regulation was comprehensively evaluated whether the regulation already regulates matters relating to ecological restoration criterias, such as biodiversity recovery, soil remediation, planting of local plants, bans on invasive plant species and monitoring and evaluation. The result showed that there was no regulation complying with all ecological restoration criterias. Meanwhile, all the regulations have mandated monitoring and evaluation after rehabilitation and reclamation activities. However, there was no regulation mandating prohibition on planting invasive plant species. In conclusion, regulations related to post coal mining rehabilitation and reclamation have not fully complied with the ecological restoration concepts, therefore improvement to that regulations are necessary.